Al-‘Alāmah al-Tijāriyyah wa Ḥimāyatuhā fī al-Qānūn al-Indūnīsī: Dirāsah Fiqhiyyah Taqwīmiyyah - Husnul Haq; Arif Ali Arif (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2020)
The trademark plays an important role in economic life, as it is a way for the merchant to distinguish his products from those produced by others. It also helps consumers to identify the products they want. Therefore, the countries of the world have agreed to conduct agreements to protect it, on top of which is the Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS). When the State of Indonesia agreed to sign this agreement, it had to provide legal cover in the field of the trademark. The research aims to demonstrate trademark protection in Indonesian law and Islamic jurisprudence. This research falls within the library search, and its description is an analytical and critical description. After careful consideration, the research concludes that Indonesian law and Islamic jurisprudence are in agreement of considering the trademark as property and right. So, they agree on the necessity of trademark protection and imposing the punishment for the aggressor. Meanwhile, they differ in the imprisonment; the law considers it as a basic punishment while Islamic jurisprudence considers it as a secondary punishment